Imbedding of the images of operators and reflexivity of Banach spaces - Vershinin, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish a criterion of reflexivity for a separable Banach space in terms of the relation between the imbedding of the images, factorization, and majorization of operators acting in this space.